2021
DOI: 10.1371/journal.pone.0247311
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter genotype modulates resting state and predator stress-induced amygdala perfusion in mice in a sex-dependent manner

Abstract: The serotonin transporter (5-HTT) is a key molecule of serotoninergic neurotransmission and target of many anxiolytics and antidepressants. In humans, 5-HTT gene variants resulting in lower expression levels are associated with behavioral traits of anxiety. Furthermore, functional magnetic resonance imaging (fMRI) studies reported increased cerebral blood flow (CBF) during resting state (RS) and amygdala hyperreactivity. 5-HTT deficient mice as an established animal model for anxiety disorders seem to be well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…3 B, D, E, G). A recent study looking at cerebral blood flow and the expression of the serotonin transporter (5-HTT) showed that, in response to an aversive predator odor, there were increases in blood flow and c-Fos expression in the CeA that were related to 5-HTT expression in males but not females [ 71 ]. These findings suggest potential sex-specific expression of serotonin receptors within the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…3 B, D, E, G). A recent study looking at cerebral blood flow and the expression of the serotonin transporter (5-HTT) showed that, in response to an aversive predator odor, there were increases in blood flow and c-Fos expression in the CeA that were related to 5-HTT expression in males but not females [ 71 ]. These findings suggest potential sex-specific expression of serotonin receptors within the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…3B, 3D, 3E, 3G). A recent study looking at cerebral blood flow and the expression of the serotonin transporter (5-HTT) showed that, in response to an aversive predator odor, there were increases in blood flow and expression of the immediate early gene c-Fos in the CeA that were related to 5-HTT expression in males but not females [44]. These findings suggest potential sex-specific expression of serotonin receptors within the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the serotonin transporter protein is also worthy of investigation as a target for many anxiolytic and antidepressant drugs. Using 5-HT transporter (5-HTT) gene-deficient mice as an anxiety animal model, researchers examined cerebral blood flow during resting and amygdala hyperresponsiveness periods using resting-state functional magnetic resonance imaging (rs-fMRI) (Kolter et al, 2021 ). The results indicated that amygdala reactivity in 5-HTT-deficient mice is regulated by the 5-HTT genotype in males.…”
Section: Sex Differences In Neurotransmitters and Neuromodulatorsmentioning
confidence: 99%
“…The results indicated that amygdala reactivity in 5-HTT-deficient mice is regulated by the 5-HTT genotype in males. Whereas, in females it is regulated by the estrous cycle and the predominant influence of gonadotropins may mask genotypic effects (Kolter et al, 2021 ).…”
Section: Sex Differences In Neurotransmitters and Neuromodulatorsmentioning
confidence: 99%